2011
DOI: 10.1111/j.1468-2389.2011.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Employability of Engineering Graduates in Campus Recruitment Drives of Indian Software Services Companies

Abstract: The purpose of this paper is to identify predictors of employability of undergraduate engineering students in campus recruitment drives of Indian software services companies. Data with respect to the academic background of 559 engineering graduates from a reputed engineering college in South India along with their performance in various non-technical training were analyzed vis-à-vis their performance in the campus recruitment drives of major Information Technology companies in India. Correlation and multiple r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 24 publications
3
16
0
1
Order By: Relevance
“…In essence, task-directed engagement and application of knowledge as indicated by Parker and Griesel (2009). These results underline those of Gokuladas (2011) which found that academic skills coupled with communication skills enhanced the employability of graduates. Additionally, a study by Nair et al (2009) found that employers indicated problem-solving skills, the ability to develop new or innovative ideas to mention a few were essential attributes of employability.…”
Section: Discussion and Recommendationssupporting
confidence: 74%
“…In essence, task-directed engagement and application of knowledge as indicated by Parker and Griesel (2009). These results underline those of Gokuladas (2011) which found that academic skills coupled with communication skills enhanced the employability of graduates. Additionally, a study by Nair et al (2009) found that employers indicated problem-solving skills, the ability to develop new or innovative ideas to mention a few were essential attributes of employability.…”
Section: Discussion and Recommendationssupporting
confidence: 74%
“…El objetivo de esta investigación fue estudiar si este programa tuvo algún impacto en el comportamiento de un grupo de variables que están consideradas como predictores de una mejor empleabilidad, de acuerdo con la literatura científica previa: (a) el rendimiento académico (Baird, 1985, Baker, 2008Brown, 1984;Gokuladas, 2011;Hassanbeigi et al, 2011;Imose and Barber, 2015;Johansen, 2014;Schick and Kunnecke, 1982;Thoms et al, 1999); (b) la participación en programas internacionales de intercambio y (c) la realización de prácticas en empresas Gault et al, 2000;Knouse et al, 1999;Knouse and Fontenot, 2008;Taylor, 1988;Weible and McClure, 2011). Se incluyó en este estudio empírico cuantitativo al total de 3,543 estudiantes matriculados en los cinco grados que ofrecieron esta innovación durante el periodo 2010-2014, principalmente estudios tecnológicos.…”
Section: Internacionalización Del Aprendizaje: Inglés Como Medio De Iunclassified
“…Some studies have demonstrated that better grades in college is likely to result in high performance in the professional world (Schick and Kunnecke, 1982) linked to the recognition by many employers that academic achievements are key predictors of job performance because abilities to perform a job, like intelligence, motivation, etc., were also present in grades (Baird, 1985;. Gokuladas (2011) showed in an empirical study, that academic variable GPA (Grade Point Average) has significant effect in enhancing employability of engineering graduates. When hiring new college graduates for engineering positions, managers in the hightech industries frequently give substantial weight to the candidate's academic background (Shick and Kunnecke, 1982).…”
Section: Theoretical Framework 1982)mentioning
confidence: 99%
See 2 more Smart Citations